[Travel journals of Edith Baring-Gould : Volume VI-VII] - Baring-Gould, Edith M. E. (Adam Matthew Digital, 1898)
An impressive series of travel journals that can be compared with those of Helen Caddick. Vol. 6 covers India, 1898-1900; v. 7 covers India and Ceylon, 1900